PENERAPAN UNSUR BUDAYA LOKAL SEBAGAI IDENTITAS TEMPAT PADA HOTEL MERCURE NEXA BANDUNG - Elfa Eprillya Fernanda; Jamaludin, Jamaludin (Department of Interior Design, Faculty of Engineering, Lancang Kuning University, Indonesia, 2024)
Hotels are accommodation facilities used for economic and tourism activities. There are various kinds of hotels with different themes and styles with their respective characteristics to attract guests. One of the things that can be highlighted from a hotel is the design. One of the things that can be used as an option is the addition of local cultural elements in the interior of the hotel. The function of adding local cultural elements to the hotel interior is to enrich the atmosphere in the hotel interior, besides adding local cultural elements can also be a means of conveying the culture where the hotel is located. In identifying this phenomenon, the Mercure Nexa Bandung hotel located on Jl. Supratman was chosen as a case study. The hotel was chosen because it was recently acquired by Accros Group in 2018 and made some new changes to its interior. The method used is descriptive analysis with identification and interpretation techniques of local cultural elements found in the interior design of Mercure Nexa Bandung hotel.